Kinematic and Aerodynamic Analysis of a Coccinella septempunctata Performing Banked Turns in Climbing Flight - Lili Yang; Zhifei Fang; Huichao Deng (Biomimetics)
Many Coccinella septempunctata flights, with their precise positioning capabilities, have provided rich inspiration for designing insect-styled micro air vehicles. However, researchers have not widely studied their flight ability. In particular, research on the maneuverability of Coccinella septempunctata using integrated kinematics and aerodynamics is scarce. Using three orthogonally positioned high-speed cameras, we captured the Coccinella septempunctata’s banking turns in the climbing flight in the laboratory. We used the measured wing kinematics in a Navier–Stokes solver to compute the aerodynamic forces acting on the insects in five cycles. Coccinella septempunctata can rapidly climb and turn during phototaxis or avoidance of predators. During banked turning in climbing flight, the translational part of the body, and the distance flown forward and upward, is much greater than the distance flown to the right. The rotational part of the body, through banking and manipulating the amplitude of the insect flapping angle, the stroke deviation angle, and the rotation angle, actively creates the asymmetrical lift and drag coefficients of the left and right wings to generate right turns. By implementing banked turns during the climbing flight, the insect can adjust its flight path more flexibly to both change direction and maintain or increase altitude, enabling it to effectively avoid obstacles or track moving targets, thereby saving energy to a certain extent. This strategy is highly beneficial for insects flying freely in complex environments.